'TAM 304' Wheat, Adapted to the Adequate Rainfall or High‐Input Irrigated Production System in the Southern Great Plains. Issue 3 (2nd July 2015) - Rudd, Jackie C.; Devkota, Ravindra N.; Ibrahim, Amir M.; Marshall, David; Sutton, Russell; Baker, Jason A.; Peterson, Gary L.; Herrington, Rex; Rooney, Lloyd W.; Nelson, Lloyd R.; Morgan, Gaylon D.; Fritz, Allan K.; et al.
Abstract : 'TAM 304' (Reg. No. CV‐1109, PI 655234), a hard red winter wheat ( Triticum aestivum L.) cultivar with the experimental designation TX01D3232, was developed and released by Texas A&M AgriLife Research in 2008. TAM 304 is an F4 –derived line from the cross TX92U3060/TX91D6564 made during the winter of 1994–1995. TAM 304 is an awned, medium‐early maturing, semidwarf wheat with white glumes. It was released primarily for its excellent grain yield potential particularly in irrigated and adequate rainfall areas across Texas and similar areas in the southern Great Plains, excellent straw strength, resistance to leaf rust (caused by Puccinia triticina Eriks.), and good milling and bread‐baking characteristics. Licensed to Scott Seed Company for marketing, TAM 304 is currently one of the most popular hard red winter wheat cultivars adapted to the adequate rainfall or high input irrigated production system in the southern Great Plains.